Sexual Functioning as a Moderator of the Relationship Between Masculinity and Men's Adjustment Following Treatment for Prostate Cancer - Shaun Michael Burns PhD; James R. Mahalik PhD (American Journal of Men's Health, 2008)
Men's enactment of traditional masculine norms may contribute to their adjustment to changes in sexual functioning following treatment for prostate cancer. In the present investigation, the authors test this hypothesis by examining the moderating role of sexual functioning on the relationship between men's adherence to masculine norms and their social, role, and mental health functioning. Results of regression analyses indicate that men with poor sexual functioning evince poor social, role, and mental health functioning when they more strongly adhere to traditional masculine norms. Participants with good sexual functioning, in contrast, exhibit positive social, role, and mental health functioning when they more strongly adhere to traditional norms of masculinity. Directions for future clinical research and treatment interventions are provided.